Antioxidant effect of valsartan in experimental model of myocardial infarction - Rozario, RJ; Akhter, N; Bhuiyan, NI; Alom, MM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):472-477 The abstract of this article is available on the PubMed website